The Effect of Annealing in a Magnetic Field on the Microstructures and Magnetic Properties of (Nd0.8RE0.2)2.2Fe12Co2B (RE = La, Ce) Alloys - Xiaohua Tan; Xuanbo Shi; Shiqi Zhang; Hui Xu (Metals)
The development of high-performance and cost-effective Nd-Fe-B permanent magnets is crucial to meet the ever-growing requirements of renewable and clean energy applications. Here, we use low-cost and highly abundant La and Ce to partially substitute Nd and investigate the effect of annealing treatment with a 1 tesla (T) magnetic field on the microstructures and magnetic properties of (Nd0.8RE0.2)2.2Fe12Co2B (RE = La, Ce) ribbons. The remanence (Br) and maximum energy product ((BH)max) of studied alloys can be improved by magnetic field annealing. The respective Br and (BH)max of annealed (Nd0.8La0.2)2.2Fe12Co2B alloy are increased to 0.86 T and 124 kJ/m3. In comparison to melt-spun (Nd0.8Ce0.2)2.2Fe12Co2B alloy, the Br and (BH)max of the magnetic field-annealed alloy are improved by 5% and 8%. The underlying mechanism of improved magnetic properties of La- and Ce-substituted alloys is different. The interaction magnetic domain size in (Nd0.8La0.2)2.2Fe12Co2B alloy can be increased by magnetic field annealing, leading to the enhancement of exchange coupling interaction, which results to the improvement in Br and (BH)max. In the (Nd0.8Ce0.2)2.2Fe12Co2B alloy, the concentration of (Fe + Co) of ferromagnetic intergranular phase is increased after magnetic field annealing, resulting in the increase in Br and (BH)max.